ANALYSIS OF RAW MATERIAL INVENTORY MANAGEMENT USING THE ECONOMIC ORDER QUANTITY (EOQ) METHOD TO DETERMINE PERIODIC ORDER QUANTITY (POQ) AT EMI BAMBANG’S OPAK FACTORY - Hanifa Lubis, Nurul (Pena Cendekia Insani, 2024)
The study aims to analyze the management of raw material inventory at Emi Bambang Opak Factory through the application of an effective method, namely Economic Order Quantity (EOQ) in determining Periodic Order Quantity (POQ). To determine the optimal order quantity, EOQ is used, while POQ is implemented to determine the efficient ordering interval. The results of this study are the determination of the POQ method at the emi bambang opak factory with a cost difference of Rp 30,717,480 for the cost of managing raw materials and ordering raw materials, this can provide solutions in more economical inventory management, to minimize the cost of storing and ordering raw materials without disrupting production continuity.